College Entrance Exam Scores and Mathematics Self-Efficacy of Prospective High School Teachers in The University of Southern Mindanao, Philippines: A Correlational Study - Ongcoy, Paul John B.; Ortiz, Ashley Coleen; Jasmin, Diana Rose; Marcelino, Jennifer; Sarad, Jericho; Tayabas, Justine Nova; Alcomendras, Mary Joy G.; Kaup, Mylene; Buenaflor, Trisha May (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: With mathematics self-efficacy and entrance exam scores being predictors of academic performance, the researchers of this study examined the relationship between these two predictors. Methodology: The instrument used for this study is the Mathematics Self-Efficacy Survey to measure the first-year prospective high school teachers’ mathematics self-efficacy. After the data were obtained, they were analyzed through the Spearman’s rank correlation coefficient to find the relationship between the two variables. Main Findings: The researchers of this study concluded that the level of mathematics self-efficacy of first-year prospective high school teachers differs, indicating that there are some areas of improvement in terms of their confidence in performing everyday math tasks, solving problems, and dealing with mathematics courses. Moreover, it is also concluded that the college entrance exam scores of prospective high school teachers do not have a significant relationship with mathematics self-efficacy. Novelty/Originality of this study: Despite the evidence that points to the predictive validity of entrance exam scores and mathematics self-efficacy on academic performance, there are limited studies concerned about the relationship between these two predictors, particularly in the context of USM students. Hence, the researchers of this study aim to delve into the possible relationship between college entrance examination scores and mathematics self-efficacy.